The Effect of the Deep Learning Approach on the Fantasy Story Writing Skills of Fifth-Grade Students - Mayang Sari Nasution; Elvina Elvina; Safrudin Safrudin; Rejeki Rejeki (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Elementary school students’ ability to write fantasy story texts still faces various obstacles, especially in developing ideas, maintaining logical flow, and using language appropriately, so a learning approach that encourages in-depth understanding is needed. This study aims to determine the effect of the deep learning approach on the fantasy story text writing ability of fifth-grade students of Public Elementary School 010 Rambah. The study adopted a quantitative, experimental approach using a One-Group Pretest–Posttest Design with one group of subjects, without a control group. Data were collected through a fantasy story text writing test given before and after the application of the deep learning approach. The results showed that students’ pretest average score was 61.38, which increased significantly to 84.52 in the posttest. This increase indicates improvements in the content, story structure, and language of students’ writing. The results of the hypothesis test using a paired t-test showed a t-value of 14.21, which is greater than the t-table value of 2.04 at a significance level of 0.05, so the null hypothesis was rejected. Thus, it can be concluded that the application of the deep learning approach significantly improves the fantasy story writing ability of fifth-grade students at Public Elementary School 010 Rambah.